Microstructure, thermal conductivity and simulation of elastic modulus of MAX-phase (Ti2AlC) gel-cast foams. Issue 10 (August 2018) - Fey, Tobias; Stumpf, Martin; Chmielarz, Anna; Colombo, Paolo; Greil, Peter; Potoczek, Marek
Abstract: MAX-phase (Ti2 AlC) gel-cast foams manufactured using agarose as gelling agent were investigated in terms of their microstructural, mechanical and thermal properties. The microstructural analysis of Ti2 AlC foams made using SEM were compared with those using X-ray micro tomography. The Young's Modulus of Ti2 AlC foams was determined using the impulse excitation technique. This experimental data was correlated with the Gibson-Ashby, Spriggs and Cross-property relation models. The thermal conductivity measurements were carried out by Laser-Flash analysis correlating to the pore network in the Ti2 AlC foam structure derived from μCT measurement. FEM-simulations of the mechanical behaviour were carried out on real structure models to determine a strut wise stress distribution under load.